IMPLEMENTASI NILAI-NILAI DEMOKRASI PANCASILA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS PROBLEM BASED LEARNING DI SEKOLAH TINGGI ILMU TARBIYAH INSIDA - Kusnadi, Asep; Fikruzzaman, Daden (LPPAIK Universitas Muhammadiyah Bandung, 2025)
Democratic values ??in higher education can be implemented through various means, such as participatory, interactive, and collaborative learning, applying the principles of deliberation and mutual respect within organizations, active involvement in student activities, and increasing democratic literacy through effective civics education. All of this is intended to shape students who are critical, possess integrity, and are responsible for their social and national lives. The purpose of this research, regarding the implementation of democratic values ??in civics courses at universities in general and specifically at the Insida Islamic Education College, encompasses both academic and practical aspects essential for developing students as responsible and character-based citizens. The research data was collected from daily observations of teaching civics courses and interviews with several students who have or are currently taking the course.